Purification, characterization and crystallization of the F-ATPase from Paracoccus denitrificans. Issue 9 (September 2015) - Morales-Rios, Edgar; Watt, Ian N.; Zhang, Qifeng; Ding, Shujing; Fearnley, Ian M.; Montgomery, Martin G.; Wakelam, Michael J. O.; Walker, John E.
Abstract : The structures of F-ATPases have been determined predominantly with mitochondrial enzymes, but hitherto no F-ATPase has been crystallized intact. A high-resolution model of the bovine enzyme built up from separate sub-structures determined by X-ray crystallography contains about 85% of the entire complex, but it lacks a crucial region that provides a transmembrane proton pathway involved in the generation of the rotary mechanism that drives the synthesis of ATP. Here the isolation, characterization and crystallization of an integral F-ATPase complex from the α-proteobacterium Paracoccus denitrificans are described. Unlike many eubacterial F-ATPases, which can both synthesize and hydrolyse ATP, the P. denitrificans enzyme can only carry out the synthetic reaction. The mechanism of inhibition of its ATP hydrolytic activity involves a ζ inhibitor protein, which binds to the catalytic F1 -domain of the enzyme. The complex that has been crystallized, and the crystals themselves, contain the nine core proteins of the complete F-ATPase complex plus the ζ inhibitor protein. The formation of crystals depends upon the presence of bound bacterial cardiolipin and phospholipid molecules; when they were removed, the complex failed to crystallize. The experiments open the way to an atomic structure of an F-ATPase complex.